Self-Assembled Thin-Layer Glycomaterials With a Proper Shell Thickness for Targeted and Activatable Cell Imaging - Zhang, Chao; Wang, Guanzhen; Han, Hai-Hao; Hu, Xi-Le; Field, Robert A.; Chen, Guo-Rong; Li, Jia; Ye, Bing; He, Xiao-Peng; Zang, Yi (Frontiers in Chemistry, 2019)
The construction of targeted and activatable materials can largely improve the precision of disease diagnosis and therapy. However, the currently developed systems either target a transmembrane antigen or are activatable to release imaging and/or therapeutic reagents intracellularly. Here we develop a simple thin-layer glycomaterial through the self-assembly between fluorescent glycoprobes, in which the carbohydrate targeting reagent and the fluorophore are linked to each other by polyethlene glycol with a suitable chain length, and thin-layer manganese dioxide. The fluorogenic material developed is both capable of targeting a transmembrane glycoprotein receptor ‘and’ fluorescently activatable by intracellular biothiols. The shell thickness of the material was determined to be important for achieving the biothiol-induced activation of fluorescence. This research might provide insight into the development of precision-enhanced self-assembled materials for disease theranostics.